2018
DOI: 10.1080/17538157.2018.1496091
|View full text |Cite
|
Sign up to set email alerts
|

Electronic patient records as a tool to facilitate care provision in nursing homes: an integrative review

Abstract: For EPR to facilitate care provision in nursing homes, consideration should be given to the type of device used for documentation, as well as the types of applications, the functionality, content, and structure of EPR. Further research exploring the experiences of end users is required to identify the optimal characteristics of an EPR system specifically for use in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
0
22
0
2
Order By: Relevance
“…EMRs intention to use by healthcare providers is an essential requirement to ensure that the expected benefits will be materialized and to predict the actual utilization of EMRs [ 22 ]. Evidences revealed that health professionals acceptance to the new system and the potential disruptions and changes that follow is one of the major barrier to implement EMR [ 23 – 25 ]. So, identifying the necessary prerequisites before the actual implementation of EMRs will help to improve the implementation status.…”
Section: Introductionmentioning
confidence: 99%
“…EMRs intention to use by healthcare providers is an essential requirement to ensure that the expected benefits will be materialized and to predict the actual utilization of EMRs [ 22 ]. Evidences revealed that health professionals acceptance to the new system and the potential disruptions and changes that follow is one of the major barrier to implement EMR [ 23 – 25 ]. So, identifying the necessary prerequisites before the actual implementation of EMRs will help to improve the implementation status.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey among nurses also suggested an association between variations in use of standardized terminologies and poor user-friendliness, with seeing electronic health records as less bene cial (31). An integrated review investigating electronic patient records as facilitator of care in nursing homes, stated a need for a focus on the type of documentation system used, and further for research among end users to identify the optimal system characteristics for use in this type of setting (32). A scoping review (33) also pointed to a general lack of research into patient safety and patient safety culture in nursing homes, and in residential care homes in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Two further components, 'structure and content', were added by the authors in order to elicit opinions on the language and structure of the EPR forms. Under each component, specific questions were developed from evidence collated from the authors' prior research [21] and designed to elicit responses about the usability of the EPR for the task.…”
Section: Interview Guidementioning
confidence: 99%
“…Despite the potential benefits associated with this technology, the EPR has been described as a burden by nursing home staff, which has been linked with issues associated with its usability [20,21]. In this study, the ISO definition of usability as 'the extent to which a product can be used by specified users to achieve specified goals with effectiveness, efficiency and satisfaction in a specified context of use' [22] is adopted.…”
Section: Introductionmentioning
confidence: 99%